Complete genome sequence of Salmonella enterica serovar Typhimurium U288 - Hooton, Steven P.T.; Timms, Andrew R.; Moreton, Joanna; Wilson, Ray; Connerton, Ian F. (American Society for Microbiology, 2013)
Salmonella enterica serovar Typhimurium U288 has firmly established itself within the United Kingdom pig production industry. The prevalence of this highly pathogenic multidrug-resistant serovar at such a critical point in the food chain is therefore of great concern. To enhance our understanding of this microorganism, whole-genome and plasmid sequencing was performed.